A class of functionals possessing multiple global minima - RICCERI, Biagio (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
We get a new multiplicity result for gradient systems. Here is a very particular corollary: Let Ω ⊂ Rn (n ≥ 2) be a smooth bounded domain and let Φ : R2 → R be a C1 function, with Φ(0, 0) = 0, such that... Mathematics Subject Classification (2010): 35J47, 35J50, 49K35.